Study on the Applicability of Barcode Loci at the Generic Level among Congeneric Species: A Genomic Approach for Quality Control in Medicinal Plants (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Debasement in the medicinal plant material is the common factor presenting negative consequences for the commercialization of medicinal plants. Both purposeful and unplanned blending and substitution of unique medication crude material with the less successful species lessens the nature of the last items. Utilization of credible and unique species is the absolute first and basic advance to deliver great quality, dependable and effectual home grown medications. Logical legitimacy of the species is the first and fundamental parameter for quality confirmation of the plant based therapeutics. Numerous customary procedures like macroscopy, microscopy and detachment of synthetic marker mixes have been utilizing since long to recognize bona fide plants and to isolate them from their adulterants. Genome based distinguishing proof strategies give an elective device which can be utilized freely or synergistically with the regular techniques. Amalgamation of DNA based methods with the customary strategies of distinguishing proof present a viable methodology for quality control and affirmation of medicinal plants.